The Dramatic treatment of the Iraqi AlHussaini theatrical text (“Al-Shammir” character as a model) - Ghazi Hussein Al-Sultani, Jamal; Mohsen Aziz Al-Husseini, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The research consists of four chapters, the first of which—which is the methodological framework for the research—included the research problem that focused on the following question: (What is the dramatic treatment of the Iraqi Al-Husseini theatrical text (Al-Shammir character as a model)? While the importance of the research was demonstrated as a cognitive achievement, it mainly benefits the playwright as well as the dramatists in general. As well as the derivation of a basic goal (the dramatic treatments of the characters are known in al-Husseini theatrical text). As for the research limits, they included temporally the texts of the Iraqi Hussaini theater for the period from 1972-2012. While the research had spatial limits, they were in Iraq. The second chapter—the theoretical framework—which included two topics—the first dealt with a historical summary of the life of Al-Shammir bin Dhi Al-Jaushan and studying the psychological dimension for this personality. As for the second topic of the theoretical framework, which is entitled (Dramatic treatment of the theatrical text of Al-Arabi Al-Hussaini, this chapter contained a set of indications obtained through the theoretical framework. The third chapter, The Research Procedures, included the research community, its samples, tools, and methodology, where the selection of samples was intentional. As for the fourth chapter, it contains the results with a presentation of the conclusions. The chapter also contains the recommendations and the suggestions, and the sources and references as well.